Analisis Sensoris Produk Stroberi Kering Beku Komersial pada E-Commerce Indonesia menggunakan Metode Deskriptif Kuantitatif - Refika Melina Putri; Mohammad Affan Fajar Falah; Annie Mufyda Rahmatika (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Fresh strawberries are rich in nutrients but have a short shelf life. Freeze-drying technology extends their shelf stability and preserves sensory quality. As freeze-dried strawberries become more popular in Indonesia, understanding consumer preferences is key for product development and competitiveness. This study characterised the sensory attributes of commercial freeze-dried strawberries in Indonesia, comparing imported Thai and local Indonesian products. Sensory evaluation involved 58 untrained panelists using a 5-point hedonic scale for seven attributes: shape, colour, aroma, taste, hardness, aftertaste, and sourness. Data were analysed using the Kruskal–Wallis nonparametric test to assess significant differences between samples. The results showed that the imported product from Thailand received the highest preference scores for taste (average score 4.17), texture (average score 4.29), aftertaste (average score 4.03), and sourness (average score 4.05). In contrast, local Indonesian products were preferred for aroma (average score 3.88), shape (average score 3.99), and colour (average score 4.12). The Kruskal–Wallis test indicated significant differences (Asymp.Sig<0,05) among samples for shape, colour, aroma, and texture attributes. These findings highlight distinct sensory preferences among Indonesian consumers and can serve as a reference for local producers to enhance product formulation, align sensory quality with market expectations, and strengthen competitiveness in the growing freeze-dried fruit industry.